Perspectives of the Kurdish knot in the Middle East - Tillo, Khoushnaw (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For centuries, Kurds have been carrying out activities aimed at obtaining their own state. Due to the cooperation of Turkey, Iraq, Iran and Syria, it was impossible in the twentieth century. As a result of Operation Desert Storm, a Kurdish enclave was created in the north of Iraq, which over the years developed and allowed for real dreams of recognized independence, at least for some of the Kurds living in the Middle East.
Keywords: Kurds; the Middle East; Arab Spring; Iraq; Kurdistan Regional Government